Pemanfaatan Teknologi Pengelolaan OPT Tanaman Sayuran Berbahan Baku Ramah Lingkungan di Kanagarian Candunang Kab Agam - Ujang Khairul; Arneti Arneti; Reflin Reflin (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2016)
Activity of use management technologogy for pest and plant disease control on vegetables based environment friendly in nagariPaninjauan Kabupaten Tanah Datar has been carried out from June toNovember 2014. This activity aims to improve farmers knowledgeabout the diseases attack of vegetables and know how to manage thedisease using biopesticide and botanic biopesticide, These activities include: Counseling and training, andevaluation. Results of monitoring the level of disease in vegetable cropsis known that those plants attacked by pest and pathogens e.i, soft rot (cabbage), anthracnosa, bacterial wilt and leaf spot (chili), tuber rot (carrots) and bacterial leaf blight and Alternaria spots (onion leaves).Attack rate ranged between 16 – 20% for disease and 15 – 30% for pest.From the activities can be take several conclusions: (1) Extent of diseasein vegetable crops in this area is high, (2) The farmers do not yetunderstand the causes of pest and plant disease ( pathogens) that attacktheir vegetable crops, (3) The farmers do not understand the methods ofdisease control using biopesticide and botanic biopesticide, (4) Theextension and field practice, have improved farmers' knowledge aboutthe management of vegetable diseases using biopesticides and botanicbiopesticide